2015
DOI: 10.1126/science.1260200
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutations and telomerase reactivation in urothelial cancer

Abstract: Reactivation of telomerase, the chromosome end-replicating enzyme, drives human cell immortality and cancer. Point mutations in the telomerase reverse transcriptase (TERT) gene promoter occur at high frequency in multiple cancers, including urothelial cancer (UC), but their impact on telomerase function has been unclear. In a study of 23 human UC cell lines, we show that these promoter mutations correlate with higher levels of TERT mRNA, TERT protein, telomerase enzymatic activity and telomere length. While pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
260
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(274 citation statements)
references
References 31 publications
12
260
1
1
Order By: Relevance
“…[45][46][47] It appears that the level of telomerase activity is the best indicator of patient prognosis. 91 In an attempt to rationalize the molecular basis for the transcriptional effects of these somatic mutations of hTERT, it was first proposed that new ETS transcription factor binding sites are generated in the duplex form of the promoter. 45 More recently it has been proposed that GABP transcription factors can be recruited to mutant promoter elements in glioblastoma multiforme, 52 thus providing an additional mechanism for the effects of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] It appears that the level of telomerase activity is the best indicator of patient prognosis. 91 In an attempt to rationalize the molecular basis for the transcriptional effects of these somatic mutations of hTERT, it was first proposed that new ETS transcription factor binding sites are generated in the duplex form of the promoter. 45 More recently it has been proposed that GABP transcription factors can be recruited to mutant promoter elements in glioblastoma multiforme, 52 thus providing an additional mechanism for the effects of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter process, TERT is required to stabilize the binding of MYC to its target gene promoters, thus affecting MYC-dependent transcriptional programs and oncogenic properties (51). It has also been recently reported that elevated TERT mRNA levels correlates with reduced disease-specific survival in urothelial carcinoma patients (22). In support of our in vitro study, we found clinical relevance in patient samples by which a significant inverse correlation was observed between ARID1A and TERT mRNA expression in ovarian clear cell carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using 23 urothelial cancer cell lines, Borah and coworkers confirmed that TERT promoter mutations correlate with higher levels of TERT mRNA, TERT protein, telomerase enzymatic activity and telomere length (Borah et al 2015). Furthermore, TERT promoter mutations also correlate with worse patient outcome and reduced disease-specific survival in two independent patient cohorts (Borah et al 2015).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 95%
“…Furthermore, TERT promoter mutations also correlate with worse patient outcome and reduced disease-specific survival in two independent patient cohorts (Borah et al 2015).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 97%
See 1 more Smart Citation